Effect of palm vitamin E,B-Carotene and *-Tocopherols on lipid oxidation and sensory quality of pound cakes. - Thed, S.T. (1995)
A trend in usage of fats and oils in baking industry is to replace plastic fats in baked goods with more unsaturated vegetable oils. Pound cake contains 30-70g fats/100g flour. Utilization of appreciable amount of unsaturated fats in pound cakes will promote oxidative deterioration during storage,resulting in the development of rancid off-flavor.changes in color,texture and nutritive properties. Inaddition to losses in quality,oxidized products may pose potential health risk. The objective of this study was to evaluate the effect of natural antioxidants on lipid oxidation and sensory quality of pound cakes. Each pound cake was prepared from 300g of wheat flour,360g of sugar,400g of margarine and 6.5g of baking powder. Percent of natural antioxidants added was 0.1%,based on the fat content of pound cake. After the cakes were baked (175C,45 min),they were stored at 25C for 0,3,6 and 9 days. Oxidation of cake samples was monitored using thiobarbituric acid test. The antioxidant activities (AOA) of various antioxidants in cake samples were calculated at the end of storage period. Sensory test was conducted to evaluate the flavor,color,texture and overall acceptability of o dy samples. Palm vitamin E exhibited the strongest inhibitory effect (AOA=0.73) on lipid oxidation of pound cakes. The AOA of combined B-carotene/*-tocopherols was significantly (*=0.005) higher than that of the individual antioxidant when used alone. A synergistic antioxidant action was also observed between these two compounds. The concentrations of antioxidants used in this study didi not affect the flavor,color and overall acceptability of cake samples,while samples containing palm vitamin E and *-tocopherols had improved texture. Lipid oxidation has been implicated in a multitude of degenerative diseases,such as cancer,cardiovascular diseases and genetic errors. The addition of these multifunctional antioxidants into pound cakes would serve to inhibit lipid oxidation,provide source of vitamins and protect consumera against diseases.